Sinergi Perguruan Tinggi dalam Memperkuat Gerakan Literasi Sekolah melalui Kurasi Donasi Buku Referensi Akademik - Dian Aswita; Maulidar Maulidar; Badratun Nafis; Saudah Saudah; Muhammad Isa (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to support the implementation of the School Literacy Movement (GLS) while escalating literacy awareness at the secondary education level. The primary issue addressed is the stagnation of literacy culture, which tends to be trapped in administrative formalities, and the lack of diverse academic references capable of bridging students' insights toward higher education. The implementation method involved interactive lectures, in-depth discussions, and a book donation campaign using a face-to-face participatory approach. The target participants included students and teachers at three institutions with heterogeneous characteristics in Banda Aceh: SMA Negeri 13 (public school), SMAS Inshafuddin (boarding-based school), and SMK Farmasi Cut Meutia (vocational school). The results showed that the distribution of reference books, thematically classified according to the specific needs of each school, significantly improved the accessibility of learning resources. Descriptive evaluation revealed high enthusiasm from participants, despite technical obstacles regarding the limited number of physical copies per title. In conclusion, this program is effective in revitalizing interest in reading and strengthening the synergy between higher education and partner schools. As a strategic step, formal cooperation (MoA) and the integration of lecturers' research books are required to ensure a more high-quality and inclusive literacy ecosystem's sustainability.